2021
DOI: 10.1089/lap.2020.0743
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic Mesogastrium Excision for Gastric Cancer: Only the Beginning

Abstract: Background: Surgery, with the aid of chemotherapy and radiotherapy, is the only curative chance for gastric cancer. Unfortunately, gastric cancer had an elevated recurrence rate, primarily locally. Mesogastrium excision (MGE) during D2 lymphadenectomy has the aim to remove all possible contaminated tissue around the stomach. Methods: PubMed, EMBASE, and the Web of Science (WOS) were systematically searched for MGE reports in gastric cancer up to March 2020. The outcome reported were the number of lymph nodes r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Moreover, even as postoperative complications were comparable between the two groups, the severity was significantly lower in the D2 + CME group. A review of the available six studies on complete mesogastric excisions on 518 patients showed that the mean number of resected lymph nodes was 36.7 ± 10 [ 46 ]. The mean operative time was 240.7 ± 10.1 min, with a morbidity rate of 6% and a median blood loss of 50.2 ± 39.6 mL.…”
Section: Gastrectomy D2 + Cmementioning
confidence: 99%
“…Moreover, even as postoperative complications were comparable between the two groups, the severity was significantly lower in the D2 + CME group. A review of the available six studies on complete mesogastric excisions on 518 patients showed that the mean number of resected lymph nodes was 36.7 ± 10 [ 46 ]. The mean operative time was 240.7 ± 10.1 min, with a morbidity rate of 6% and a median blood loss of 50.2 ± 39.6 mL.…”
Section: Gastrectomy D2 + Cmementioning
confidence: 99%